Konsep Pendidikan Era Medsos: Analisis Dimensi Hifdz din Menurut Luqman al-Hakim Dengan Pendekatan Maqasidi - Siti Fahimah; Nihlatut Toyibah; Nuriyah Rohmanah (Program Studi Ilmu Al Quran dan Tafsir Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2022)
The reality of changing times that continue to move dynamically in several countries, especially in Indonesia, has a significant impact on the decline of moral values. Various changes and developments of the times affect the styles and patterns of human life today. In this era of social media not only has a positive impact but also has a negative impact. Through this paper, the author will try to further analyze the dimensions of hidfz ad-din in the story of Luqman Al-Hakim in the Qur'an of Luqman verses 13-19 and how these educational values ​​can be implemented in the current era of social media. To carry out this analysis, the author will use a maqashidi interpretation approach which will seek to reveal the maqashid dimensions and qur'ani values ​​in the Qur'an Surah Luqman verses 13-19. In this study, the author will try to highlight the story of Luqman Al-Hakim using a maqashidi interpretation approach to find the maqashid behind Luqman al-Hakim's advice to his son. The author hypothesizes that Luqman al-Hakim's advice contains educational principles that are important to reveal and develop as an educational model offer to face the era of social media as it is today. In the Qur'an letter Luqman verses 13-19 the author understands that Luqman Al-Hakim's advice is important to be applied to the education system. From some of the advice contained in it, there are 3 big points, namely: aqidah education, worship education and moral education.